"An Exploratory Study of Balanced Score Card - Strategic HR Perspective" - Sarangi, Swatee; Saluja, Divya (SFIMAR Research Review, 2010)
The changes in the business environment with increasing globalization, changing demographics of the workforce, increased focus on profitability through growth, technological changes, and intellectual capital with focus on knowledge workers and the never-ending changes that organizations are undergoing have led to increased importance of managing human resources (Devanna, Fombrum, &Tichy, 1981, Wright, 1998). In this complex and dynamic business environment, a Human Resource system that is highly administrative and lacks strategic integration fails to provide the competitive advantage needed for survival, thus losing its relevance. Youndt and Snell (1996) find that firms employing HR practices according to the stated strategy are regarded to have better perceptual performance. Strategic HRM can help HR transform from a Cost centre to an Investment centre in true sense. The Balanced Score Card technique introduced by Robert Kaplan and David Norton in 1992 as a performance measurement framework added strategic non-financial performance measures to traditional financial metrics to give organizations a more ’balanced’ view of their performance. It can be used and applied at both the individual and the organisational level. This paper unravels the application of Balanced Score Card as a strategic HR tool in organizations drawn from various sectors. It also suggests a holistic theoretical model where Balanced Scorecard through its human resource initiatives and processes can help nurture organizations talent pool in a way that is congruent with its goals; so that the business achieves sustainable competitive advantage.